A CLINICAL TRIAL ON THE EFFICACY OF BHALLATAKADI LEPA IN CHARMAKEELA W.S.R. CUTANEOUS WARTS - Pahadiya, *Lokendra; Swapna, B. (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda described few diseases under the heading of Kshudra roga. Charmakeela is one of them and it is simple and does not cause threat to life but it has a cosmetic problem, which results in considerable distress to the patients when they are seen on face and exposed part of the skin. Bhallatakadi lepa has prepared for this study. Total 15 patients suffering from Charmakeela (Warts)were selected for study, 5 patients dropped out due to various regions and remaining 10 patients treated with Bhallatakadilepa. The duration of the trial was one month with a further follow up of two months. The data collected was statistically analyzed for the interpretation of results. Bhallatakadilepa was found not effective in reducing number of warts or size of warts. Though mild ASRs (Application site reactions), including pruritus, irritation or burning sensation, erythema, hyper and hypopigmentation and LSRs (Local skin reactions) including dryness or scaling, hyperpigmentation, hypopigmentation, irritation or burning sensation and erythema were seen in some of the patients. So the conclusion of the study is that the lack of efficacy of the trial drug may be attributed mainly to the seasonal variations in the drug collection, drug potency and drug adulteration from market places, which were practically inevitable during this research work. The research may also consider a longitudinal / prospective study in order to obtain complete analysis of the drug.